Dividend Policy and Market Performance of Listed Manufacturing Companies in Nigeria - Oniyama , Morrison E.; Olaoye , Samuel Adebayo; Ogundajo , Grace O. (Journal of Accounting and Finance, 2021)
Interest in shareholders’ value is gaining momentum as a result of several recent developments in the business environment. Basically, it is a critical decision and quite challenging for the managers to decide on an appropriate and ideal dividend policy to adopt, that will improve shareholders’ wealth. In such decision dilemma, the managers are faced with the decision of whether to pay dividend or to plough back distributable earnings into the business. Therefore, this study examined the effect of dividend policy on shareholders’ wealth. The result of the multiple regression analysis conducted revealed that dividend policy had significant effect on market price per share; dividend yield exerted significant negative effect on share price, dividend per share had significant positive effect on share price; while dividend pay-out ratio negatively but insignificantly influenced market share price. Managers should ensure that optimal decision is attained in the choice of the portion of distributable profits to be given as returns on shareholders’ investment as this is germane in attaining its wealth maximization objective.